Assessment of the molecular mechanisms of action of novel 4-phenylpyridine-2-one and 6-phenylpyrimidin-4-one allosteric modulators at the M1 muscarinic acetylcholine receptors - van der Westhuizen, Emma T.; Spathis, Arthur; Khajehali, Elham; Jörg, Manuela; Mistry, Shailesh N.; Capuano, Ben; Tobin, Andrew B.; Sexton, Patrick M.; Scammells, Peter J.; Valant, Celine; Christopoulos, Arthur (ASPET, 2018)
Positive allosteric modulators (PAMs) that target the M1 muscarinic acetylcholine (ACh) receptor (M1 mAChR) are potential treatments for cognitive deficits in conditions such as Alzheimer's disease and schizophrenia. We recently reported novel 4-phenylpyridine-2-one and 6-phenylpyrimidin-4-one M1 mAChR PAMs with the potential to display different modes of positive allosteric modulation and/or agonism (Mistry et al., 2016), but their molecular mechanisms of action remain undetermined. The current study compared the pharmacology of three such novel PAMs with the prototypical first-generation PAM, BQCA, in a recombinant Chinese hamster ovary (CHO) cell line stably expressing the human M1 mAChR. Interactions between the orthosteric agonists and the novel PAMs or BQCA suggested their allosteric effects were solely governed by modulation of agonist affinity. The greatest degree of positive co-operativity was observed with higher efficacy agonists, whereas minimal potentiation was observed when the modulators were tested against the lower efficacy agonist, xanomeline. Each PAM was investigated for its effects on the endogenous agonist, ACh, on three different signalling pathways, (ERK1/2 phosphorylation, IP1 accumulation and β-arrestin-2 recruitment), revealing that the allosteric potentiation generally tracked with the efficiency of stimulus-response coupling and that there was little pathway bias in the allosteric effects. Thus, despite the identification of novel allosteric scaffolds targeting the M1 mAChR, the molecular mechanism of action of these compounds is largely consistent with a model of allostery previously described for BQCA, suggesting that this may be a more generalized mechanism for M1 mAChR PAM effects than previously appreciated.